Association between of Parental Socialization on Elementary Students' Physical Activity Levels in Murcia Region - Antonio Sánchez- Urrea; Alberto Gómez-Mármol; Salvador Baena-Morales; Tomás Izquierdo-Rus (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In this quantitative study, we investigated how parenting styles affect the physical activity habits of Elementary School students in the Region of Murcia. Sedentarism is a growing problem in today's society, especially among children. Method. Two questionnaires were used under a quantitative approach, the IPAQ and the ESPA29, to collect data from 937 students from different educational centers in order to discover the reality in children's society and its relationship with physical activity. Results. Parental socialization styles affect the physical activity of students, and significant differences were found between democratic, neglectful, permissive, and authoritarian styles with physical activity. Conclusions. It is important to take into account parenting styles in promoting healthy physical activity habits in Elementary School students, and educational implications and new lines of research on this topic are suggested.